Blessing and destruction: Climate change and trajectories of blame in Northern Ghana = Bénédiction et destruction - Irit Eguavoen (University of Bonn, Center for Development Research (ZEF), 2012)
This anthropological study provides an analysis of environmental observations by farmers and their perceptions of change, as well as models of blame in Northern Ghana, a poor agricultural region of high vulnerability to climate change. Qualitative data were collected through a standardized questionnaire which was directed to twenty-five individuals to collect data on community consensus on how to explain this change. Responses were transcribed to allow content analysis. Natural data sets confirmed most local observations but older age and affectedness of the respondents were crucial in determining the views of the respondents. Farmers observed more changes than younger people who were not yet decision-makers on their family farms. Climate change was generally given a lower priority by the respondents compared with other manifestations of change that have occurred over the past decades, such as infrastructural development, human-spiritual relations and changes in social relations within the community. When referring to these changes, the respondents often made reference to the blessing of the land and the destruction of the land. The destruction of the land was always understood in a metaphorical way as the result of eroding social relationships and stagnation, as well as norm-breaking and lack of unity within the community.
Keywords: 330; Climate change; perception; local priorities; West Africa